ENVIRONMENTAL IMPACT ANALYSIS OF QUARRYING ACTIVITIES IN SUNGAI DUKU, PADANG PARIAMAN, IN TERMS OF BIOLOGICAL COMPONENTS - Farhanah Shofwah Verina; Vauzia Vauzia; Khairunisa Khairunisa; Ardelia Febriana (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
Non-metallic mineral and rock (category or class C) mining activities have the potential to generate significant environmental impacts, particularly on biological components. This study aims to assess the impact of class C mining activities in the Duku River, Padang Pariaman. A qualitative descriptive analysis method was employed, with data collected through observation, documentation, and interviews conducted at the study site. Based on the results, the flora diversity index calculated using the Shannon–Wiener method was 2.218, while the fauna diversity index was 2.186. These values fall within the moderate category of biodiversity. Therefore, it can be concluded that class C mining activities in the Duku River have a measurable impact on biological components.